TINJAUAN HUKUM WARIS TERHADAP ANAK PERNIKAHAN POLIGAMI YANG DIADOPSI OLEH ISTRI PERTAMA MENURUT KOMPILASI HUKUM ISLAM - Ericha Fristianti (Universitas Islam Kadiri, 2022)
Judicial review is a final legal remedy filed by the convict or his heirs. However, in the practice of criminal justice in Indonesia, remedies reconsideration may be filed by the Public Prosecutor. This is because in the Article 263 paragraph (1) does not expressly ban the public prosecutor to file a reconsideration. Hence, in several Supreme Court decisions allowed for the public prosecutor to file a reconsideration. This paper aims to analyze the reasons for the Prosecution filed a reconsideration and review of the draft regulation by the Public Prosecutor to come. This paper is based normative research, the approach of legislation, case-based approach, and comparative approach. According to the research explained that the reason for the Prosecution filed a judicial review due to new evidence (novum), the presence of acquittal or off, and the decision in the sentencing judgment when there is no evidence of a criminal act. In order ensuring legal certainty for the public prosecutor to file a reconsideration should be set in a legislation. This is possible because there is enactment of new Criminal Procedure Code.